Association between maternal anthropometry and term newborn weight. Cienfuegos, 2020-2021 - Greta Margarita Arrechea García; Adys Castro Barberena; Georgina Jiménez Estrada; Ivette Gómez Fernández; Ariadna Peréz Morales; Maydelis Gómez Valdivia (Medisur)
Background: maternal anthropometric indicators constitute a useful tool in the prognosis of possible unfavorable results in relation to the product of conception nutritional evaluation. Objective: to determine the relationship between the maternal anthropometric nutritional status and the newborn at term weight. Methods: a descriptive study was carried out in 66 pregnant women and their newborns, from January 2020 to December 2021, at the Octavio de la Concepción y de la Pedraja Polyclinic, in Cienfuegos. Maternal variables: age, weight, height, gestational body mass index, overall weight gain, and mean arm circumference; in addition to the weight of the newborn were considered. Basic descriptive statistics and Pearson's correlation coefficient were calculated. Results: adolescents (n=42), maternal malnutrition (n=32), deficient global weight gain and pregnant women evaluated as low weight by the values of the mean arm circumference predominated. Low maternal weight was associated with 57.1% and 20.8% of low birth weight newborns of adolescent and adult mothers, respectively. These variables showed an association with the birth of a newborn underweight or with insufficient weight. Conclusions: there is a relationship between the maternal anthropometric nutritional status and the newborn at term weight. The maternal variables most associated with the underweight birth were: age less than 19 years, poor body mass index, low overall weight gain, and mean arm circumference values > 5 and ≤ 10 percentile.